Prediction of residual stress regeneration in multi-pass milling. Issue 5 (March 2016) - Fergani, Omar; Jiang, Xiaohui; Shao, Yamin; Welo, Torgeir; Yang, Jianguo; Liang, Steven
Abstract Machining-induced residual stress is important for the part performance. In the literature, various predictive models have been proposed for residual stress in one-pass machining without considering the multi-pass aspect. This study describes the regeneration of residual stress in multi-pass machining with thermo-mechanical loadings, in the full elasto-plastic state, captured using the Neumann-Duhamel principle. The residual stress is then analysed satisfying elastic-plastic relaxation in-between layers and at the boundaries. Large experimental data in milling of AA2121-T3 agreed well with model predictions, thus supporting the consideration of initial stress functions, materials cyclic plasticity and compatibility to allow for residual stress prediction in multi-pass machining.